Toxic metal exposure as a possible risk factor for COVID-19 and other respiratory infectious diseases. (December 2020) - Skalny, Anatoly V.; Lima, Thania Rios Rossi; Ke, Tao; Zhou, Ji-Chang; Bornhorst, Julia; Alekseenko, Svetlana I.; Aaseth, Jan; Anesti, Ourania; Sarigiannis, Dimosthenis A.; Tsatsakis, Aristides; Aschner, Michael; Tinkov, Alexey A.
Abstract: Multiple medical, lifestyle, and environmental conditions, including smoking and particulate pollution, have been considered as risk factors for CO ronaVI rus D isease 2019 (COVID-19) susceptibility and severity. Taking into account the high level of toxic metals in both particulate matter (PM2.5) and tobacco smoke, the objective of this review is to discuss recent data on the role of heavy metal exposure in development of respiratory dysfunction, immunotoxicity, and severity of viral diseases in epidemiological and experimental studies, as to demonstrate the potential crossroads between heavy metal exposure and COVID-19 severity risk. The existing data demonstrate that As, Cd, Hg, and Pb exposure is associated with respiratory dysfunction and respiratory diseases (COPD, bronchitis). These observations corroborate laboratory findings on the role of heavy metal exposure in impaired mucociliary clearance, reduced barrier function, airway inflammation, oxidative stress, and apoptosis. The association between heavy metal exposure and severity of viral diseases, including influenza and respiratory syncytial virus has been also demonstrated. The latter may be considered a consequence of adverse effects of metal exposure on adaptive immunity. Therefore, reduction of toxic metal exposure may be considered as a potential tool for reducing susceptibility and severity of viral diseases affecting the respiratory system, including COVID-19. Graphical abstract: Image 1